1981
DOI: 10.1084/jem.154.4.1033
|View full text |Cite
|
Sign up to set email alerts
|

T cell-mediated immunosuppression as an obstacle to adoptive immunotherapy of the P815 mastocytoma and its metastases.

Abstract: The numerous reports (1) showing that suppressor T cells are generated in response to growth of immunogenic tumors serve to provide an explanation for the paradoxical growth of these tumors in their immunocompetent syngeneic hosts. A recent publication (2) from this laboratory revealed, for example, that progressive growth of a transplantable murine tumor, the Meth A fibrosarcoma, results in the generation in the host of a T cell-mediated state of immunosuppression that prevents the regression of this tumor by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 6 publications
3
52
0
Order By: Relevance
“…They show that it is only in the former that intravenously infused immune T cells are able to give rise to the production of an adequate number of cytolytic effector T cells. On the basis of results of previous studies (3,4), which showed normal tumor bearers possess T cells that can suppress the expression of adoptive immunity in TXB recipients, it was postulated that failure of passively transferred immune T ceils to cause tumor regression and give rise to the generation of an adequate number of cytolytic T cells in normal tumor-bearing recipients is due to the presence in these recipients of suppressor T cells. This was investigated by determining whether spleen cells from donors with established P815 tumors are capable, on passive transfer, of inhibiting the generation of cytolytic T cells in T cell-deficient tumor-bearing recipients of immune spleen cells.…”
Section: Inhibition Of Adoptive Cytolytic T Cell Production By Supprementioning
confidence: 99%
See 1 more Smart Citation
“…They show that it is only in the former that intravenously infused immune T cells are able to give rise to the production of an adequate number of cytolytic effector T cells. On the basis of results of previous studies (3,4), which showed normal tumor bearers possess T cells that can suppress the expression of adoptive immunity in TXB recipients, it was postulated that failure of passively transferred immune T ceils to cause tumor regression and give rise to the generation of an adequate number of cytolytic T cells in normal tumor-bearing recipients is due to the presence in these recipients of suppressor T cells. This was investigated by determining whether spleen cells from donors with established P815 tumors are capable, on passive transfer, of inhibiting the generation of cytolytic T cells in T cell-deficient tumor-bearing recipients of immune spleen cells.…”
Section: Inhibition Of Adoptive Cytolytic T Cell Production By Supprementioning
confidence: 99%
“…The need for T cell-deficient tumor-bearing recipients to demonstrate successful adoptive immunotherapy suggested the existence in normal tumor bearers ofa T cell-dependent mechanism that prevents intravenously infused sensitized T cells from expressing their antitumor function. Evidence that this obstacle to adoptive immunotherapy is a tumor-induced, T cell-mediated mechanism of immunosuppression was supplied by the demonstration (3,4) that the passive transfer of splenic T cells from normal tumor bearers prevents passively transferred tumor-sensitized T cells from causing tumors to regress in T cell-deficient recipients. It was hypothesized, on the basis of this and other evidence (5) that the growth of an immunogenic tumor results in the generation of a state of T cell-mediated immunosuppression that functions to "down-regulate" a preceding concomitant immune response.…”
mentioning
confidence: 99%
“…BALB/c TCR tg ("6.5") mice expressing a TCR specific for amino acids 110 to 120 of influenza hemagglutinin (HA) were a generous gift from Dr H. von Boehmer (Dana-Farber Cancer Institute, Boston, MA). 14 6.5 mice on a Thy1.1 ϩ/ϩ , Thy1.1 ϩ /Thy1.2 ϩ , or Rag2 Ϫ/Ϫ background were used in experiments where indicated. Experiments were conducted in accordance with protocols approved by the Animal Care and Use Committee of the Johns Hopkins University School of Medicine.…”
Section: Micementioning
confidence: 99%
“…[5][6][7][8][9] Indeed, we previously reported the paradoxical observation that mice with established B-cell lymphoma that underwent transplantation with marrow and lymphocytes from syngeneic tumor-bearing donors had superior progression-free survival to identical cohorts receiving grafts from non-tumorbearing donors. Mature postthymic T cells from the tumor-bearing donors were an essential component of the graft in mediating this effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation